Urban Ekoriparian: Pemberdayaan Kelompok Rentan di Bantaran Sungai Ciliwung oleh PT Pertamina Patra Niaga AFT Halim Perdanakusuma - Tumansery, Andreas; Maulana, Wahyu; Sidiq, Ilham; Nofadila, Tefy; Sirait, Joshua Yoga Frans; Yunisha, Afifah Nur; Islami, Ivon Dewinda (Journal of Administration, Governance, and Political Issues, 2024)
Pertamina Patra Niaga AFT Halim Perdanakusuma is a fuel distribution company located in Jakarta. Pertamina AFT Halim Perdanakusuma is actively implements corporate social responsibility programs, one of them is Urban Ekoriparian located in Cawang Village Kramat Jati Sub District, East Jakarta. Located on the banks of the Ciliwung river, Cawang Village with its densely populated housing, is at hish risk of flooding. A significant issue faced by the community is the widespread disposal of waste along the riverbanks. In response to this problem, PT Pertamina Patra Niaga AFT Halim Perdanakusuma initiated the Urban Ekoriparian program and targeting vulnerable groups as program beneficiaries. This research aims to know how the CSR Urban Ekoriparian program conducted by PT Pertamina Patra Niaga Halim Perdanakusuma operates in Cawang Village. Methods used in this research was a descriptive qualitative method. The analysis results show that the Urban Ekoriparian Program targets Kelompok Saung as the program implementer, involving several activities such as urban farming and disaster training. The company actively engages the community in every stage, from planning to implementation and monitoring. The vulnerable groups involved in this program include the elderly and impoverished community. The conclusion of this research indicates that the Urban Ekoriparian program provides benefits to the community in terms of the environment, economy, and socio-cultural aspects.